Were the public security policies implemented by the last administration in Bogota efficient? Analysis of the perception of citizens (2017)
The citizens of Bogotá have manifested through several surveys, their negative perception regarding security in the country's capital. Therefore, the obligation to investigate, analyze and propose actions, to improve the situations that affect adversely the population belongs directly to the City Hall to the Council. The most important tool that these entities have to intervene and implement actions to mitigate the insecurity are called "Public Policies", which have specific and efficient actions that help to protect the citizens’ interests. It will be necessary to evaluate the strategies executed by the former Administration, to identify how efficient was the "Bogota Humana", from the Mayor Gustavo Petro, regarding to homeland security.